Exosomal MIF Derived From Nasopharyngeal Carcinoma Promotes Metastasis by Repressing Ferroptosis of Macrophages - Chen, Wenhui; Zuo, Fan; Zhang, Kaiwen; Xia, Tian; Lei, Wei; Zhang, Zixiang; Bao, Lili; You, Yiwen (Frontiers in Cell and Developmental Biology, 2021)
Nasopharyngeal carcinoma (NPC) is the most common malignant tumor of the head and neck cancer (HNC). Metastasis is the main cause of treatment failure. However，the molecular mechanism for NPC metastasis is still unclear. As one of the most common host immune cells in the tumor microenvironment, macrophage has been proven to regulate metastasis. And, exosomes are the important bridge connecting various cells in TME. Currently, the role of NPC-exos on macrophages and their impact on metastasis remains to be unexplored. In this study, we found that MIF is highly expressed in NPC cells, and the exosomes secreted by NPC cells can be taken up by macrophages, thereby，inhibiting the ferroptosis of macrophages, and then promoting the metastasis of NPC. Targeting MIF may be a potential treatment to reduce the rate of metastasis.